2015
DOI: 10.1021/acs.jpcb.5b01417
|View full text |Cite
|
Sign up to set email alerts
|

Ion Hydration and Association in Aqueous Potassium Phosphate Solutions

Abstract: Ionic hydration and ion association in aqueous solutions of KH2PO4, K2HPO4, and K3PO4 at 25 °C up to high concentrations have been investigated using dielectric relaxation spectroscopy (DRS). The three phosphate anions were found to be extensively hydrated, with total hydration numbers at infinite dilution of ~11 (for H2PO4(-)), ~20 (HPO4(2-)), and ~39 (PO4(3-)). These values are indicative of the existence of a second hydration shell around HPO4(2-) and especially PO4(3-). Two types of hydrating water molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
135
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(151 citation statements)
references
References 65 publications
16
135
0
Order By: Relevance
“…To obtain deeper insights into the hydration state of the pNIPAm chains, we evaluate effective hydration numbers per monomer unit using the generalized Cavell equation [43][44][45],…”
Section: Hydration/dehydration Behaviormentioning
confidence: 99%
“…To obtain deeper insights into the hydration state of the pNIPAm chains, we evaluate effective hydration numbers per monomer unit using the generalized Cavell equation [43][44][45],…”
Section: Hydration/dehydration Behaviormentioning
confidence: 99%
“…Water molecules tend to aggregate around salts in aqueous solution to hydrate them. In fact, phosphates are known to produce strong structure‐forming ions in water, having a coordination number reported as 39 . This could lead to a decrease in the number of water molecules available for interaction with NVP molecules resulting in an increase of unfavorable monomer/monomer interactions and a further decrease in the propagation rate constant and in the rate of polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent dielectric relaxation studies on hydrated phosphates indicate interactions extend into a full second solvation shell. 33 Although previous neutron diffraction studies have revealed extended ion–water interactions, 36 experiments with hydrated phosphate salts show no evidence for ionic influences beyond direct coordination to the ion. 30 The dynamic nature of water molecules makes probing weak ion-induced structural effects beyond a rigid inner shell a challenging endeavor.…”
Section: Introductionmentioning
confidence: 95%
“…The distance to which ion-induced solvent orientation can extend has been studied in solution using multiple techniques, including diffraction, 29,30 spectroscopy 3133 and theory. 34,35 Although ion-induced structuring of water molecules within the coordination shell is unambiguous, there have been conflicting interpretations amongst these results as to whether ion–water interactions can extend beyond the first solvation shell.…”
Section: Introductionmentioning
confidence: 99%